Understanding brain waste: Unequal opportunities for skills development between highly skilled women and men, migrants and nonmigrants. Issue 5 (25th February 2021) - Riaño, Yvonne
Abstract: Brain waste studies seldom analyse the skills development of tertiary‐educated workers according to gender and country of origin. Combining statistical analyses, participatory workshops and 77 qualitative interviews on employment trajectories with highly skilled workers in Switzerland, I offer three contributions. An intersectional perspective reveals unequal opportunities of skills development: Swiss‐born men have the highest rates of employment, income and jobs commensurate with their education, followed by foreign‐born men, then Swiss‐born women and lastly foreign‐born women. Second, a multiscalar perspective shows how actions by individuals, families, employers and the state favour or constrain skills advancement among women and men. Individual perceptions of gender roles and unequal childcare responsibilities within couples constrain women's skills development. Further constraints are set by the state and employers' policies and practices regarding migration, childcare, taxation and hiring. Third, a spatial–temporal perspective unveils that gender inequalities arise at particular moments (migration and childbirth) and places (lacking childcare services and limited employment).